Система Гражданского Права в России и Ее Сопоставление с Другими Правовыми Системами (Civil Law System in Russia and Its Comparison with Other Legal Systems) - Bisay, Ocrella Trisella Vera; Nur, Rohim; Paramitasari, Shinta (Jurnal Cita Hukum, 2023)
This article explores the civil law system in Russia and compares it with other legal systems. The main focus is on the historical roots and influence of the Roman-Continental legal system in the formation of Russian civil law. By analyzing the Russian Civil Code, this article investigates the structure, principles, and unique characteristics of the Russian civil law system. Comparisons are made with the common law legal system, the Islamic legal system, and the socialist legal system that previously influenced Russia during the Soviet Union. The comparative results highlight essential differences in approaches, legal sources, and the role of courts between these systems. This article has the potential to provide in-depth insights into the evolution and context of civil law in Russia, as well as its implications in the global legal framework.